Neurochemical measurements in the zebrafish brain - Jones, Lauren; McCutcheon, James; Young, Andrew; Norton, William (Frontiers in Behavioral Neuroscience, 2015)
The zebrafish is an ideal model organism for behavioural genetics and neuroscience. The high conservation of genes and neurotransmitter pathways between zebrafish and other vertebrates permits the translation of research between species. Zebrafish behaviour can be studied at both larval and adult stages and recent research has begun to establish zebrafish models for human disease. Fast scan cyclic voltammetry (FSCV) is an electrochemical technique that permits the detection of neurotransmitter release and reuptake. In this study we have used in vitro FSCV to measure the release of analytes in the adult zebrafish telencephalon. We compare different stimulation methods and present a characterisation of neurochemical changes in the wild-type zebrafish brain. This study represents the first FSCV recordings in zebrafish, thus paving the way for neurochemical analysis of the fish brain.